Gambaran Kinerja Kader Filariasis dalam Program Pengobatan Massal Filariasis di Wilayah Kerja Puskesmas Brebes Kabupaten Brebes - Putri, Fanindita Widyantoro; Martini, Martini; Saraswati, Lintang Dian; Ginandjar, Praba; Kusariana, Nissa (Jurnal Ilmiah Mahasiswa, 2021)
Mass Drug Administration (MDA) of filariasis is effort for filariasis elimination. Brebes Regency is one of the endemic areas for filariasis which started MDA in 2017. However, it has not yet reached the target results for mass treatment coverage. This study aims to describe the performance of elimination personnel in the implementation of the mass administration program for filariasis in the working area of Brebes Health Center, Brebes Regency. This study used a cross sectional research method. The population in this study were all elimination personnel in the work area of Brebes Health Center, Brebes Regency who were registered in 2019. The sample size in this study was 120 respondents. The sampling technique used proportional random sampling. The results showed that elimination personnel in recording the assisted families (93,3%), elimination personnel in selecting target family members to be treated is optimal (73,3%), elimination personnel in helping puskesmas determine the dosage and administration of medicines for each of the assisted families (52,5%), elimination personnel in recording the assisted families who drank the medicine on the card was optimal (63,3%), and elimination personnel in monitoring and recording treatment reactions that may arise and reporting to health workers was optimal (53,3%).Â